COMPUTER TECHNOLOGY OF ANALYSIS AND DESIGN OF A BUILD ENVIRONMENT FROM THE POINT OF ITS VISUAL PERCEPTION - Булгакова, Т. В.; Полякова, О. В.; Кисіль, С. С.; Шмельова, О. Є. (Art and Design, 2020)
The purpose of the investigation is the development of computer technology of analysis and design of built environment from the point of its visual perception in the space of its three-dimensional model without using the perspective projections. The methodology were used to achieve the purpose: analysis of the scientific publications on the topic of object environment composition; applied geometry methods, method of division of the geometrical object into simplexes (triangulation), methods of advanced algebra and analytical geometry; computer modeling for construction of the model of visual perception of the environment. Methods of analysis of the three-dimensional model on the basis of modeling of visual perception by means of computer technologies directly in the area of the model without using perspective projections are developed. It is offered to analyze the visual perception of any objects and their relations by means of using the solid angles with the vertices placed in the point of view and the surfaces that surround the visible contours of three-dimensional objects. This approach gives the opportunity to analyze the objects simultaneously regardless their position according to the observer; apart of that, the objects, which are accepted similarly in the reality, will have the same geometrical features during the modeling of visual perception and beside that, the refusal of using of the perspective projections will make possible to avoid the distortion of the images. The algorithm of determination of the solid angles to three-dimensional objects, which is the basis of computer methods of compositional analysis of the object environment from the position of visual perception without the use of perspective projections, is developed. The geometrical model of visual perception by a human being from the certain point of perception is built. It makes possible to define correctly visual features of the object environment and gives the opportunity to analyze the whole surrounding of the observer in the area of 360 degrees. Scientific novelty of the investigation means that the methods of analysis of the three-dimensional model on the basis of modeling of visual perception by means of computer technologies directly in the area of the model without using perspective projections are developed for the first time. The concept of the geometrical model of visual perception by a human being from the certain point of perception is developed. The further development of the methodology of quantitative determination of characteristics of object environment by means of computer technologies is defined. Practical significance shows that the results of the scientific investigation can be used for analysis and judgments of the aesthetic peculiarities of the object environment by means of computer technologies with quantitative determination of characteristics of object environment from the point of its visual perception. Such approach gives the opportunity to develop and create the further certain recommendations and instructions for correction of the existing environment and for the development of the new one.